2018
DOI: 10.3390/catal8030111
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Mn/Co Binary Metal Catalysts Supported on Two Commercial Diatomaceous Earths for Oxidation of Benzene

Abstract: Two commercial diatomaceous earths were used as supports for the preparation of Mn/Co binary metal catalysts at different metal loads (5 to 10 wt % Mn and 5 to 15 wt % Co) by incipient wetness deposition. The activity of the prepared catalysts towards the complete oxidation of benzene to CO 2 and water was investigated between 100 and 400 • C. Raw supports and synthesized catalysts were characterized by XRD, N 2 physisorption, SEM-EDS, H 2 -TPR, and TPD. The purification treatment of food-grade diatomite signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…The observed temperature for 100% complete benzene oxidation over Pt FANaX is higher than this of Pt/Al 2 O 3 catalysts [51], and it is compatible with this of Au and Pd catalysts loaded on iron modified cerium oxides [52,53] and Mn/Co binary catalysts [54] and cobalt-cerium oxides [55]. The advantages are the utilization of fly ash from one side and a cheap source for the preparation of zeolite support from the other side.…”
Section: Resultssupporting
confidence: 65%
“…The observed temperature for 100% complete benzene oxidation over Pt FANaX is higher than this of Pt/Al 2 O 3 catalysts [51], and it is compatible with this of Au and Pd catalysts loaded on iron modified cerium oxides [52,53] and Mn/Co binary catalysts [54] and cobalt-cerium oxides [55]. The advantages are the utilization of fly ash from one side and a cheap source for the preparation of zeolite support from the other side.…”
Section: Resultssupporting
confidence: 65%
“…This mineral crystallizes in the form of regular octagonal crystals. Due to its properties, it is used for the treatment of fireproof fabrics as well as for clarifying cloudy water [ 56 , 57 , 58 , 59 ]. Alum is used in the synthesis of synthetic ethyl alcohol, but scientific literature lacks a large amount of information on the catalytic use of alum.…”
Section: Introductionmentioning
confidence: 99%
“…3,24−26 Actually, diatomite is mainly composed of bio-SiO 2 , is abundant, and is very cheap. 27,28 In addition, as a natural material, it exhibits mesoporosity/macroporosity structure, strong acid resistance, good thermal stability, and low thermal conductivity, which make it very promising to directly use as an efficient support. 27,29,30 Hence, in this work, natural diatomite supported Pt NP catalysts were fabricated through using Cinnamomum camphora (CC) leaf extract as the reducing agent, which was further applied in the oxidation of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Zhang et al found that Pd NPs can be anchored well on natural diatomite and presented excellent activity for the Heck and Suzuki reaction. But there are nearly no reports about using diatomite supported metal NPs in the removal of VOCs, and the previous works were mainly concentrated on its role as adsorbent for VOC removal due to the hierarchically porous structure and higher adsorption capacity. , Actually, diatomite is mainly composed of bio-SiO 2 , is abundant, and is very cheap. , In addition, as a natural material, it exhibits mesoporosity/macroporosity structure, strong acid resistance, good thermal stability, and low thermal conductivity, which make it very promising to directly use as an efficient support. ,, …”
Section: Introductionmentioning
confidence: 99%